Funkcje partykuły „no” w dziecięcych wypowiedziach mówionych - Matuszewska, Izabela (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2014)
It was important for the study to determine the frequency of the analysed part of speech. As a result of investigation of the linguistic material it has been demonstrated that nowadays the particles constitute 12.8% of the wordforms used by children. The particle no represented 2.2% of the total of used words. The obtained results have been compared with the data collected during similar research, which was completed thirty years ago (7.5% – all particles, 1.6% – the particle no). On the basis of a comprehensive analysis and the comparison of research results, it can be concluded that in the contemporary spoken Polish of children there occurred a visible increase in the use of particles. This, in turn, may be a symptom of the impoverishment of the Polish language.